Communication Management Strategy in iNews Tv Makassar Promotional Ads - Muhammad Reynaldhy Mutfah; Muh. Akbar; Kahar (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Although digitalisation and social media have changed the advertising landscape, television remains one of the traditionally effective communication platforms to reach a wide audience. As a medium that offers high visibility and significant impact, television plays an important role in communication strategies, especially in the context of promotional advertising. This research aims to identify and analyse the communication management strategies implemented by iNews TV Makassar in managing promotional advertisements. Using a descriptive qualitative method, this study collected data through observation, in-depth interviews, and documentation to describe the practices and dynamics that occur. The main findings show that the main strategy implemented by iNews TV Makassar is effective advertisement management, which involves intensive cooperation with clients to ensure that they keep choosing iNews TV Makassar as their advertising platform. Quality of service is the main focus, with an emphasis on fulfilling the needs and wants of ad users as well as accuracy in delivering messages to match the expectations of ad agents. This research reveals the importance of good relationship management with ad users and service customisation to achieve optimal client satisfaction, which in turn contributes to the success of advertising promotion at iNews TV Makassar.Keywords: Communication Management Strategy, Promotional Advertising, iNews Tv Makassar